Relationship between mucin gene polymorphisms and different types of gallbladder stones - Gongqing Ren; Yongmao Fan; Ruizi Zhong; Gang Zou; Xiaojun Huang; Yue Zhang (BMC Medical Genomics)
Abstract Background Gallstones, a common surgical condition globally, affect around 20% of patients. The development of gallstones is linked to abnormal cholesterol and bilirubin metabolism, reduced gallbladder function, insulin resistance, biliary infections, and genetic factors. In addition to these factors, research has shown that mucins play a role in gallstone formation. This study aims to explore the connection between different types of gallstones and mucin gene polymorphisms. Methods For this purpose, a total of 121 patients with gallbladder stones PNS and 107 patients with healthy controls PNS were enrolled in this case–control study. One SNPs (rs4072037) of MUC1 gene、 three SNPs (rs2856111、rs41532344、rs41349846) of MUC2 gene、four SNPs (rs712005、rs2246980、rs2258447、rs2259292) of MUC4 gene、seven SNPs (rs28415193、rs56047977、rs2037089、rs2075854、rs3829224、rs2672785、rs2735709) of MUC5 gene、eight SNPs (rs10902268、rs61869016、rs573849895、rs59257210、rs7396383、rs74644072、rs7481521、rs9704308) of MUC6 gene、five SNPs (rs10229731、rs73168398、rs4729655、rs55903219、rs74974199) of MUC17 gene. We amplified SNP sites by polymerase chain reaction (PCR) using specific primer sets followed by DNA sequencing. Results The frequencies of MUC2 rs2856111 C/T genotype (OR = 3.81, 95%CI: 1.06–13.68) was higher than the control group. MUC17 rs10229731 A/C genotype (OR = 0.33, 95%CI: 0.12–0.95), rs73168398 G/A genotype (OR = 0.26, 95%CI: 0.07–0.98), MUC6 rs10902268 G/A genotype (OR = 0.40, 95%CI: 0.17–0.95) at lower frequencies than controls. The frequencies of MUC2 rs41532344 T allele (OR = 2.55, 95%CI: 1.06–6.13), MUC4 rs712005 G allele (OR = 2.51, 95%CI: 1.20–5.22), MUC5B rs2037089 C allele (OR = 3.54, 95%CI: 1.14–11.01) and MUC5AC rs28415193 G allele (OR = 1.77, 95%CI: 1.02–3.07) were higher than the control group. MUC6 rs10902268 A allele (OR = 0.004, 95%CI: 0.00–0.27), rs61869016 C allele (OR = 0.07, 95%CI: 0.01–0.63) at lower frequencies than controls. Conclusions Polymorphisms in the mucin gene were linked to the formation of gallbladder stones. The MUC4 rs712005 G allele, MUC5B rs2037089 C allele, MUC2 rs41532344 T allele and MUC5AC rs28415193 G allele were found to predispose individuals to the development of the disease. MUC6 rs10902268 A allele and rs61869016 C allele were identified as protective factors. Meanwhile, MUC2 rs2856111 CT genotype was found to predispose individuals to the development of the disease. MUC17 rs10229731 AC genotype, rs73168398 GA genotype and MUC6 rs10902268 GA genotype were identified as protective factors.